2014
DOI: 10.1063/1.4861740
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration-induced back stress in critical solder length for three-dimensional integrated circuits

Abstract: Because of the miniaturization of electronic devices, the reliability of electromigration has become a major concern when shrinking the solder dimensions in flip-chip joints. Fast reaction between solders and electrodes causes intermetallic compounds (IMCs) to form, which grow rapidly and occupy entire joints when solder volumes decrease. In this study, U-grooves were fabricated on Si chips as test vehicles. An electrode-solder-electrode sandwich structure was fabricated by using lithography and electroplating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Therefore, the supply of Cu increased the growth of the interfacial IMC at the anode. The stress gradient during electromigration is commonly known as "back stress" [30]. It was found that the anode underwent the highest compressive stress due to the accumulation of the atoms.…”
Section: Interfacial Intermetallic Compound (Imc) Under Electromigration and Thermal Ageingmentioning
confidence: 99%
“…Therefore, the supply of Cu increased the growth of the interfacial IMC at the anode. The stress gradient during electromigration is commonly known as "back stress" [30]. It was found that the anode underwent the highest compressive stress due to the accumulation of the atoms.…”
Section: Interfacial Intermetallic Compound (Imc) Under Electromigration and Thermal Ageingmentioning
confidence: 99%
“…The increased resistance, even a broken circuit caused by electromigration, could lead to severe reliability problems. While the technology has progressed significantly in recent years thanks to extensive developmental efforts, related studies have identified a few areas of concern that are critical challenges [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their research on [ 34 ] Sn−Ag−Cu lead−free solder joints, Guo et al found that the diffusion rate of atoms, such as Cu and Ag, along the β−Sn grain, with a body−centered tetragonal structure (a = b = 0.583 nm, c = 0.318 nm) on the c−axis (<0.01> crystal phase), is much greater than that on the a− and b−axes, and the angle θ between the c−axis and the electron flow direction has a significant impact on the service life of micro−solder joints under electromigration. In their study on the relationship between electromigration damage and Sn grain orientation in Cu/Sn/Cu solder joints, Huang et al [ 35 ] found that the IMC tends to separate at the β−Sn boundary at the small angle between the c−axis of the β−Sn grains and the electron flow. The dissolution of the cathode IMC is also affected by β−Sn grain orientation control.…”
Section: Introductionmentioning
confidence: 99%